2020
DOI: 10.1007/s00170-020-04945-3
|View full text |Cite
|
Sign up to set email alerts
|

On the impacts of tool geometry and cutting conditions in straight turning of aluminum alloys 6061-T6: an experimentally validated numerical study

Abstract: Aluminum alloys 6061-T6 are widely utilized in the automotive, aerospace and marine industries due to high corrosion resistance, high strength, and good workability and machinability. The machining performance of these alloys depend on several factors including tool's material, coating and geometry.Cutting tool edge radius is one of the most effective factors in cutting forces, energy requirement and chip formation during metal cutting. The present article aims to study the interactions between the cutting edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 22 publications
(34 reference statements)
0
50
0
Order By: Relevance
“…As observed in this figure, the resultant machining forces increased with raising feed rate for both modes. This is because higher feed rates lead to larger tool–chip contact area and pressure, resulting in larger magnitudes of machining forces [ 9 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As observed in this figure, the resultant machining forces increased with raising feed rate for both modes. This is because higher feed rates lead to larger tool–chip contact area and pressure, resulting in larger magnitudes of machining forces [ 9 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Orthogonal cutting of aluminum alloys is an important machining operation in the aerospace industry, particularly as initial step for further and more complex operations. According to Javidikia et al [ 9 ], one of the major challenges in othrogonal cutting of aluminum alloys is the occurrence of non-uniform cutting temperatures and machining forces. A previous research study by Hu and Huang [ 10 ] on turing of AISI4340 steel demonstrated that machining forces and temperature are the fundamental factors that determine the extent of residual stresses and tool wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also showed that cutting forces increase with an increase in feed rate and depth of cut. A similar study was completed by Javidikia et al [ 10 ]. They studied the impact of tool geometry and cutting conditions in turning the aluminum alloy 6061-T6 under a dry condition with uncoated carbide insert.…”
Section: Literature Reviewmentioning
confidence: 75%
“…According to Pattnaik et al [2], excessive crater wear was noticed while machining non-ferrous materials because of continuous chip flow over the outside of the tool. Javidikia et al [3] revealed that a larger contact region of the toolchip builds the chip thickness proportion that prompts to have higher cutting temperatures. Likewise, it induces a higher cutting force that prompts an effective utilization of the machine.…”
Section: Introductionmentioning
confidence: 99%